Enhanced Absolute Accuracy of an Industrial Milling Robot Using Stereo Camera System. (2016) - Möller, Christian; Schmidt, Hans Christian; Shah, Nihar Hasmukhbhai; Wollnack, Jörg
Abstract: In this publication an approach for increasing the absolute positioning accuracy of an industrial milling robot with help of a stereo camera system is presented. To measure the position and orientation of the robot tool center point, a specific adapter with retro reflective markers is mounted on the spindle. The calculation of the transformation of this target holder to the robot tool is part of this paper along with the calibration from the robot to the camera system. These datasets serve as the basis of a static pose control, where the robot absolute accuracy errors will be greatly reduced.